Natural based hydrogels promote chondrogenic differentiation of human mesenchymal stem cells - Zahedi Tehrani, Tina; Irani, Shiva; Ardeshirylajimi, Abdolreza; Seyedjafari, Ehsan (Frontiers in Bioengineering and Biotechnology, 2024)
Background: The cartilage tissue lacks blood vessels, which is composed of chondrocytes and ECM. Due to this vessel-less structure, it is difficult to repair cartilage tissue damages. One of the new methods to repair cartilage damage is to use tissue engineering. In the present study, it was attempted to simulate a three-dimensional environment similar to the natural ECM of cartilage tissue by using hydrogels made of natural materials, including Chitosan and different ratios of Alginate. Material and methods: Chitosan, alginate and Chitosan/Alginate hydrogels were fabricated. Fourier Transform Infrared, XRD, swelling ratio, porosity measurement and degradation tests were applied to scaffolds characterization. After that, human adipose derived-mesenchymal stem cells (hADMSCs) were cultured on the hydrogels and then their viability and chondrogenic differentiation capacity were studied. Safranin O and Alcian blue staining, immunofluorescence staining and real time RT-PCR were used as analytical methods for chondrogenic differentiation potential evaluation of hADMSCs when cultured on the hydrogels. Results: The highest degradation rate was detected in Chitosan/Alginate (1:0.5) group The scaffold biocompatibility results revealed that the viability of the cells cultured on the hydrogels groups was not significantly different with the cells cultured in the control group. Safranin O staining, Alcian blue staining, immunofluorescence staining and real time PCR results revealed that the chondrogenic differentiation potential of the hADMSCs when grown on the Chitosan/Alginate hydrogel (1:0.5) was significantly higher than those cell grown on the other groups. Conclusion: Taken together, these results suggest that Chitosan/Alginate hydrogel (1:0.5) could be a promising candidate for cartilage tissue engineering applications.